Pemanfaatan Media Realia untuk Meningkatkan Aktivitas dan Prestasi Menulis Pantun pada Siswa Kelas IV SDN 1 Sukabumi Indah Bandar Lampung TP 2019/2020 - Jarwani Jarwani (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
The purpose of this study was to describe the increased activity and learning achievement of Pantun using environmental media in Grade IV students of SD Negeri 1 Sukabumi Indah TP 2019/2020. The method used in this research is Classroom Action Research (CAR) through 3 cycles and 3 meetings in each cycle. The research subjects were Grade IV Semester 1 students at SDN 1 Sukabumi Indah Bandar Lampung for the 2019/2020 academic year. which totaled 30 students. The data were obtained from the record of the observer's observation sheet on the learning process planned by the researcher, the observation sheet of learning activities and the test sheet to determine learning achievement and the observer's observation of the learning carried out by the researcher. Based on the findings and results of the discussion, the use of environmental media can increase activity and achievement in learning to write rhymes for Class IV Semester 1 students at SDN 1 Sukabumi Indah Bandar Lampung TP 2019/2020.